Competing Mechanisms with Limited Commitment - Suehyun Kwon (Center for Economic Studies and ifo Institute (CESifo), 2016)
This paper studies competing mechanisms with limited commitment over infinite horizon. Between a mechanism and the agent, there is perfect monitoring, but each mechanism can have arbitrary signals about the interaction between other mechanisms and the agent. I show that if the agent's type is common knowledge, any individually rational payoffs can be sustained in a perfect Bayesian equilibrium. If the agent's type is his private information, Pareto frontier of mechanisms' payoffs can be obtained by repeating the static optimal screening every period; in particular, price posting with the static optimal price is the optimal mechanism. The complete information case is a strong form of folk theorem while the incomplete information case shows that folk theorem breaks down with private information even as the discount factor goes to one. Results hold with any finite number of mechanisms, any discount factor and any monitoring technology including private monitoring.
Keywords: 330; competing mechanisms; limited commitment; private monitoring; price posting; folk theorem